Analisis Semiotika Foto Cerita Jurnalistik Haze Word Press Photo Contest 2022 Karya Abriansyah Liberto - Krisna Aldrin Gunawan; Sumaina Duku; Kararek (CV. ITTC INDONESIA, 2023)
This thesis is entitled